Dose and temporal effects on gene expression profiles of urothelial cells from rats exposed to diuron - Ihlaseh-Catalano, Shadia M. [UNESP]; Bailey, Kathryn A.; Cardoso, Ana Paula F. [UNESP]; Ren, Hongzu; Fry, Rebecca C.; Camargo, João Lauro Viana de [UNESP]; Wolf, Douglas C. (Elsevier B.V., 2014)
Diuron (3-(3,4-dichlorophenyl)-1,1-dimethylurea) is a substituted urea herbicide that at high dietary levels (2500 ppm) induces rat urinary bladder hyperplasia after 20 weeks of exposure and neoplasia after 2 years. The effects on the urothelium after short-term exposure have not been described. The present 7-day study evaluated the dose-dependency of urothelial alterations in the urinary bladder using light microscopy, scanning electron microscopy, and genome-wide transcriptional profiling. Male Wistar rats were fed 0,125, 500, 2500 ppm diuron for 7 days. The urinary bladder and isolated urothelial cells of these animals were processed for microscopic examination and gene expression profiling, respectively. No significant treatment-related morphologic effects were observed. The number of differentially expressed genes (DEGs) in the exposed groups increased with diuron levels. Diuron-altered genes involved in cell-to-cell interactions and tissue organization were identified in all treatment groups. After 7 days of diuron exposure, transcriptional responses were observed in the urothelium in the absence of clear morphologic changes. These morphological findings are different from those observed in a previous study in which 20 weeks of diuron exposure was associated with simple hyperplasia secondary to the persistent cytotoxicity and necrosis associated with continuous cellular regeneration. Comparison of the gene expression profiles of rats exposed to the 2500 ppm carcinogenic diuron dose for 7 days versus 20 weeks revealed few similarities between these two time points at the gene or pathway level. Taken together, these data provide insight into the dose- and temporal-dependent morphological and transcriptional changes associated with diuron exposure that may lead to the development of tumors in the rat urinary bladder. (C) 2014 Elsevier Ireland Ltd. All rights reserved.
Keywords: Diuron; Rat urinary bladder; Carcinogenesis; Gene expression profiling; Microarray analysis; Cell adhesion